Framework para desenvolvimento de tactical shooters em realidade virtual - Barbosa, Ícaro da Silva (2024)
In recent years, Extended Reality technologies have seen significant development, with the release of more affordable and computationally powerful Head-Mounted Displays, allowing for more elaborate simulations than before. One of the most lucrative genres in the gaming market is Shooters, with five out of the top ten grossing games on Steam in 2023 being Shooters. As game development is a challenging activity that demands time and effort, frameworks are needed to help reduce development time and effort, increase code maintainability, and make it easier to understand. Given the scarcity of frameworks for developing Tactical Shooters in Virtual Reality in the literature, this work aims to propose a framework for these games. All the steps for creating a framework were followed, including model definition, architecture definition, and framework development. Three prototypes were developed: two based on the architecture and one utilizing the framework. To validate the framework’s usability, a workshop with game developers was held, culminating in a focus group interview with all participants. As a result, it is intended to promote the creation of new works that use Virtual Reality and frameworks for Tactical Shooters.